DIVISION OF AUTHORITY AND POWERS BETWEEN SUBJECTS OF THE RUSSIAN FEDERATION AND MUNICIPAL FORMATIONS IN SPHERE OF DEVELOPMENT OF TOURISM - Sergeev D. B. (Scientific Journal of Pedagogy and Economics, 2019)
By this article the fundamental scientific task addressed is to develop a unified, logically consistent understanding of the nature of scientific problems related to political and legal aspects of the implementation of the powers of state authorities of the subjects of the Russian Federation and local self-government bodiesin sphere of tourism development, as well as studying the current state studies of political and legal aspects of the implementation of the powers of state bodies of the subjects of the Russian Federation andlocal self-government bodies in sphere of tourism development. The analysis, synthesis and legal methods were used in the study of the division of authority and powers between subjects of the Russian Federation and municipal formations in the sphere of development of tourism. The study reveals, in Russian federal laws, division of authority and powers between subjects of the Russian Federation and municipal formations in the sphere of development of tourism development is based on a fragile balance that is based on ambiguously interpreted norms of the Constitution of the Russian Federation.